Odpowiedź :
Odpowiedź:
a) 6a - 25 a = (-4)
6* (-4) - 25 = -24 - 25 = -49
b) 40 - 3x dla x= 9
40 - 3 * 9 = 40 - 27 = 13
c) 5a +7b dla a= (-3) i b= 4
5 * (-3) + 7 * 4 = -15 + 28 = 13
d) 2k - 6m dla k= (-8) i m=(-3)
2 * (-8) - 6 * (-3) = -16 - 18 = -34
Mam nadzieję, że odpowiedź jest pomocna
Czekam na naj :D
Szczegółowe wyjaśnienie:
Odpowiedź:
a) 6a - 25 = - 49
b) 40 - 3x = 13
c) 5a +7b = 13
d) -2k - 6m = 34
Szczegółowe wyjaśnienie:
a) 6a - 25 dla a = (-4) 6*(-4) - 25 = - 24 - 25 = - 49
b) 40 - 3x dla x= 9 40 - 3*9 = 40 - 27 = 13
c) 5a +7b dla a= (-3) i b= 4 5*(- 3 ) +7* 4 = - 15 + 28 = 13
d) -2k - 6m dla k= (-8) i m=(-3) -2* (- 8 ) - 6* ( - 3 ) = 16 + 18 = 34